Utilization of Phone Simulations to Assess Competency Within Nursing Education. Issue 5 (8th September 2022) - Wilbeck, Jennifer; Cross, Lacey; Weaver, Angela; Kennedy, Betsy B.
Abstract : Background: Phone simulations offer educators unique opportunities for teaching and assessment with reduced scheduling and location barriers. Problem: Challenges to learner assessments are multifaceted, including decreased availability of clinical sites, preceptors, and, at times, clinical instructors. Approach: This article describes the creation and implementation of diverse phone simulations at multiple levels of nursing education and provides suggestions for broader replication and adaptation. Outcomes: Phone simulations are easily implemented, well received, and helpful in assessing student learning and progression. At the generalist level, telephone SBAR (situation, background, assessment, and recommendation) simulations promote essential communication skills imperative in the delivery of safe and effective care. For advanced practice learners, phone simulations are easily applied across multiple populations and specialties. Guided reflections following simulation offer learners an opportunity to immediately self-remediate. Conclusions: Phone simulations provide adaptable opportunities to support learning and assess knowledge and competency within educational and clinical settings.